SPECULATIVE REALISM IN THE SEARCH OF LOST INDEPENDENT OBJECTS - Ігор КАРІВЕЦЬ (Епістемологічні дослідження у філософії, соціальних і політичних науках)
The article examines the peculiarities of the approach of speculative realism to the analysis of the concepts of existence and object in the context of its criticism of Kantian and post-Kantian ontology, and especially the concept of correlationism, the dependence of the existence of objects on the perception of subjects, i.e. the postulation of the impossibility of the existence of the objective and the independent world from a man. The reasons for the emergence of speculative realism in contemporary French and English philosophy and why these philosophies are called post-continental philosophies are clarified with the help of the historical-comparative method and the method of analysis. In opposition to correlationism, speculative realism seeks to “break through” to a “non-human world,” that is, to a world that is non-anthropocentric and non-human-dimensional. Such a world would be, in fact, “alien” to man, because it would be filled with objects unknown to man and independent of him. Here the obvious goal of speculative realism is to grant freedom to objects through the destruction of correlationism. In addition, the article shows that speculative realism, as a phenomenon in contemporary philosophy, is not homogeneous. Object-oriented ontology, speculative materialism, and materialist phenomenology can be distinguished in it. All these sub-ontologies of speculative realism demonstrate semantic shifts in the understanding of object and existence, but they recognize the existence of objective reality or the reality of objects, regardless of what they mean by the latter, which they try to ground it, in order to give it a fundamental meaning. Therefore, common for these sub-ontologies is the name “speculative” or “metaphysical” realism.